Interpersonal interaction: phenomenological characteristic of basic parameters (Actual Problems of Psychology in Educational Institutions, 2021)
In the article, the author examines the phenomenologicalcharacteristics of the basic parameters of interpersonal interaction basedon three pairs of subject-subject and subject-object relations: dominancesubmission, positivity-negativity, and success-failure. The emphasis is onthe study of interpersonal interaction and social behavior of people using avariety of methods. An analysis of the concepts of T. Leary, R. Mulluniemi,G. Junе allows us to conclude that they can be considered as acceptablefor practice, but not as empirical-theoretical confirmed models.
Keywords: phenomenology, basic parameters, interpersonal interaction, interpersonal relations